The Association between Body Fat Percentage and Incidence of Prehypertension among Medical Student - Aliza Shavela; Mariani (Fakultas Kedokteran Universitas Sriwijaya, 2020)
INTRODUCTION. The prevalence of prehypertension in Indonesia is 48,4%. Obesity is one of the risk factors fordeveloping prehypertension. Obesity can be measured using body fat percentage. A high body fat percentage will increasethe level of plasma angiotensinogen, renin, the activity angiotensin-converting enzyme, and aldosterone. These factors contribute to higher blood pressure. This study aims to determine whether there is a significant association between body fat percentage and incidence of prehypertension.METHODS. This study is an analytic study with cross-sectional study approach. Data collection was carried out with a total of 106 respondents aged around 17- 22 years. This researched was conducted from August to September 2019 at the Faculty of Medicine and Health Science of Atma Jaya. The research data were collected through filling out a demographic questionnaire, blood pressure measurement using sphygmomanometer, and body fat percentage measurement using bioelectrical impedance analysis. Bivariate analysis of the association between gender and blood pressure, the association between gender and body fat percentage, and the association of body fat percentage with blood pressure were analyzed using the chi-square method.RESULTS. The bivariate analysis shows that there is a significant association between gender and blood pressure (p=0,001), the association between gender and body fat percentage (p=0,000) and the association between body fat percentage and the incidence of prehypertension (p=0,000) with OR = 3,992CONCLUSION. A high body fat percentage is a risk factor for developing prehypertension.